1994
DOI: 10.1002/bit.260431116
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of aspartame precursor with an immobilized thermolysin in tert‐amyl alcohol

Abstract: N-(Benzyloxycarbonyl)-L-aspartyl-L-phenylalanine methyl ester (Z-AspPheOMe), a precursor of the synthetic sweetner asparatame, was synthesized from N-(benzyloxycarbolyl)-L-aspartic acid (Z-Asp) and L-phenylalanine methyl ester (PheOMe) with an immobilized thermolysin in various organic solvents. We found that in tert-amyl alcohol containing a small amount of water the immobilized enzyme showed a high activity comparble to that in ethyl acetate with quite a high stability. The immobilized enzyme was fully stabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…The comparable catalysis rate of aspartame and sucrose ester synthesis suggests that the latter reaction is enzymatic. In agreement with Nagasayu et al, aspartame synthesis could not be observed using DMSO as the solvent [16]. Polyols are known to stabilise proteins [17] and studies of thermolysin have shown that small carbohydrates contribute to the hydration and activation of the enzyme [18].…”
Section: Resultssupporting
confidence: 82%
“…The comparable catalysis rate of aspartame and sucrose ester synthesis suggests that the latter reaction is enzymatic. In agreement with Nagasayu et al, aspartame synthesis could not be observed using DMSO as the solvent [16]. Polyols are known to stabilise proteins [17] and studies of thermolysin have shown that small carbohydrates contribute to the hydration and activation of the enzyme [18].…”
Section: Resultssupporting
confidence: 82%
“…These rates indicate that the specific activity of thermolysin in these reactions was around 12-fold higher than the industrial-grade Thermoase. These rates were also much higher than comparable thermolysin reactions in organic solvents, which were in the range of 2 to 10 nmol min −1 mg −1 (e.g., Nagayasu et al, 1993b). The yields of up to 80% product conversion were clearly higher than in comparable aqueous systems, which were usually well below 50% (e.g., Inouye, 1992;Murakami et al, 1996;Zhou and Huang, 1993).…”
Section: Thermolysin-catalyzed Synthesis Of Z-gln-leu-nh 2 and Z-asp-mentioning
confidence: 80%
“…Based on the available literature, the aspartame precursor Z-Asp-Phe-OMe is probably the most investigated model dipeptide. Enzymatic synthesis methods have used aqueous (e.g., Inouye, 1992;Murakami et al, 1996;Zhou and Huang, 1993), biphasic (e.g., Hirata et al, 1997;Murakami and Hirata, 1997;Nagayasu et al, 1993b), and organic-phase systems (e.g., Nagayasu et al, 1993a;Nakanishi et al, 1985) in both continuous (e.g., Hirata et al, 1997;Nakanishi et al, 1990) and batch mode (e.g., Inouye, 1992;Nagayasu et al, 1993b). Most of these methods have some drawbacks, usually either low yields or low reaction rates.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies on long-term stability have been carried out in organic media under continuous operation using R-chymotrypsin (5,6) and thermolysin (7)(8)(9)(10)(11)(12)(13). And there are a few studies on operational stability in repeated batch operation using thermolysin CLECs (14) and immobilized R-chymotrypsin (15)(16)(17) in organic solvents.…”
Section: Introductionmentioning
confidence: 99%